Graphene: Hexagonal Boron Nitride–Graphene Heterostructures: Synthesis and Interfacial Properties (Small 1/2016). Issue 1 (January 2016) - Li, Qiucheng; Liu, Mengxi; Zhang, Yanfeng; Liu, Zhongfan
Abstract : The front cover of this special issue is contributed by Y. F. Zhang, Z. F. Liu, and co‐workers, who describe the synthesis and interface properties of graphene and hexagonal boron nitride heterostructures. Both in‐plane (h‐BN‐G) and vertically stacked (G/h‐BN) heterostructures have attracted intense attention for energy‐band engineering and device performance optimization for graphene. On page 32, this review article encourages further investigation of the related novel properties, as well as the application versatility of these materials.